Neuromarketing readiness in Malaysia: where are we now? / Azrin Ali ... [et al.] - Ali, Azrin; Putit, Lennora; Mohamad Arshad, Azlin Shafinaz; Kamall Khan, Yasmin; Hendryati, Heny (Faculty of Business and Management, 2024)
In the race to forecast consumer behaviours and purchase patterns, a culmination of new ideas, theories, and research is brought forth and used. One such contemporary study on consumer behaviour is the subject of neuromarketing. An underlying theme among several key concepts in defining neuromarketing is the ability to measure consumers’ brain activities; it aims to understand the reasoning and reactions toward specific offerings. Although the field of study has garnered worldwide interest, the subject of neuromarketing is only starting to gain traction in Malaysia, with only a few existing literatures observed. This study plans to assess the readiness of companies in Malaysia to implement neuromarketing as part of their overall strategic marketing plan, as well as the comfort level of companies in deploying neuromarketing to increase the effectiveness of the companies’ performance. By applying mixed-method research, several small to medium-sized enterprises (SMEs) would be selected to explore and subsequently examine their comprehension, readiness, and implementation of neuromarketing.